ANALISIS PEMASARAN KETELA POHON (Manihot Esculenta) DI DESA SIALANG RAMPAI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Devi Arnela; Eliza Eliza; Shorea Khaswarina (Indonesian Journal of Agricultural Economics, 2019)
The purpose of this study was to (1) find out marketing function and marketing channel of cassava, (2) analyze cost, margin, efficiency marketing and farmer share of cassava. The method used in this research is survey method with technique of sample selection by Random Sampling method. Technique of marketing institution by Snowball Sampling method. The result showed there is two marketing channel, channel I is farmer-collecting merchants-consumer and  channel II is farmer-home industry. The result of this research showed that the marketing cost in channel I is Rp 48,59 and in  channel II is Rp. 27,00. Efficiency marketing in I channel is 1,62% and channel II is 1,57% that means channel II is more efficient. Margin is in channel I. Farmer share channel I is 56,27% and channel II is 100%.